A self-balance system for naval operation vehicles. (March 2019) - Kuo, C S; Lee, F C; Huang, C Y; Chu, H C; Cheng, C C
Abstract: For the purpose of maintaining the balance of the deck of naval vehicles while they are maneuvering on the water surface, a simple mechanism with a feedback control scheme is designed to detect and compensate the external disturbances. To avoid complex mathematical modeling for high degree-of-freedom mechanism, a simplified mechanism adopted from the novel Stewart and delta designs is developed. Incorporating with the inertial measurement unit (IMU), the proposed framework is able to drive the mechanism by servomotors to achieve the goal of balancing the vessel deck by detecting instant three-axis attitude data. Field experiments performed at a swimming pool demonstrated outstanding performance in deck balance by suppressing external disturbance from the wave.